If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + 13 = x + 6 Reorder the terms: 13 + -1x = x + 6 Reorder the terms: 13 + -1x = 6 + x Solving 13 + -1x = 6 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 13 + -1x + -1x = 6 + x + -1x Combine like terms: -1x + -1x = -2x 13 + -2x = 6 + x + -1x Combine like terms: x + -1x = 0 13 + -2x = 6 + 0 13 + -2x = 6 Add '-13' to each side of the equation. 13 + -13 + -2x = 6 + -13 Combine like terms: 13 + -13 = 0 0 + -2x = 6 + -13 -2x = 6 + -13 Combine like terms: 6 + -13 = -7 -2x = -7 Divide each side by '-2'. x = 3.5 Simplifying x = 3.5
| 21d=-63 | | 56x=-218 | | M=57 | | -5y+10x=-15 | | 168=-6(8x-4) | | 4p(p+2)=0 | | 665/7 | | 4(n-3)=28 | | -3(-3+5x)=-6 | | -7(2x-6)=154 | | -9x+5x=16 | | 6(-3+2b)=-90 | | V=pir^2h2/3 | | -5(-7+3x)=-70 | | x(800+x)x(100+30)= | | 625=3.14(r^2) | | -123=-3(7x-8) | | -6(x+1)-13=21+8 | | 92=-4(7a-2) | | 6(3r-2)-6=-90 | | 7x^2-14x+7=0equation | | b=2/3ac | | g(x)=3x^2-6x-2 | | 12m^2+11m-18=0 | | -129=-8(6b-1)+7 | | p^2+7p+71=0 | | x^3+17x^2-16x-6=0 | | 8w=20 | | 102=(x-12)+(x+18) | | -8x+10=-5x+4 | | 800+100+30=0 | | 7(1-7x)-5x=-371 |